African monsoons Part 1 : Climatological structure and circulation - SARA, KSHUDIRAM; SAHA, SURANJANA (MAUSAM, 2001)
A recent (1979-1996) NCEP/NCAR reanalysis dataset is utilized to study the structure and characteristics of the time-mean meteorological fields over the continent of Africa and surrounding oceans during February and August when the seasonal monsoons are normally at their peak intensity. The vertical structure, revealed in zonal and meridional sections over different parts of the continent, bring out the dominant influences of the neighbouring oceans and topography in the formation and distribution of monsoon troughs and ridges and associated dry and wet zones. Vertical circulations reveal a symbiotic relationship between the tropical monsoons and the subtropical deserts of the two hemispheres. Some salient features of the African monsoons, such as the formation of double equatorial troughs and their movement following change of season, are discussed and compared with similar features observed elsewhere over the world.